ANALISIS PEMAHAMAN NASABAH BNI SYARIAH TENTANG KE‘SYARIAH’AN BNI SYARIAH (Studi Kasus BNI Syariah Godean, Sleman, Yogyakarta) - Shofa Rabbani (University of Darussalam Gontor, 2013)
Islamic banking must be based on the principles of Islamic economics framework in accordance with Islamic law. Islam forbids usury and interest, but Islam has permitted profit and loss sharing. This research aims to analyze the influence of the level of people’s understanding toward Islamic banking, usury, interest and profit and loss sharing, and to analyze the relationship of Islamic Bank Customer Savers which are also Conventional Bank Customer Savers. This research involved 51 respondents, all of whom are based on customers of BNI Sharia. The result of the study showed that the level of people’s understanding toward Islamic banking is still relatively low. Their perception of how sharia Islamic banks, usury, interest, and the profit and loss sharing are varies, most of them still do not understand and know these terms. On the other side, the relationship between Islamic Bank Customer Savers which are also Conventional Bank Customer Savers and employment status and education level is closely associated. This has an impact on the public interest to save or take financing in Islamic banks is also lower. Islamic banks which supposed to be a prominent choice for the Muslim community is still inferior to conventional bank dominance. Thus, they need to evaluade themselves forward in order to increase the number of customers. Socialization is not only done by banking practitioners in banking settings, but it may be given by dai / khatib / preachers in mosques, formal and informal meetings.